Reinforced concrete structures - Samson, Charlie (Oryson Press, 2024)
Reinforced concrete is a composite material in which concrete’s relatively low tensile strength and ductility are counteracted by the inclusion of reinforcement having higher tensile strength and/or ductility. The reinforcement is usually, though not necessarily, steel reinforcing bars (rebar) and is usually embedded passively in the concrete before the concrete sets. Reinforcing schemes are generally designed to resist tensile stresses in particular regions of the concrete that might cause unacceptable cracking and/or structural failure. Modern reinforced concrete can contain varied reinforcing materials made of steel, polymers or alternate composite material in conjunction with rebar or not. Reinforced concrete may also be permanently stressed (in compression), so as to improve the behaviour of the final structure under working loads. One of the most common methods of doing this are known as pre-tensioning and post-tensioning. Concrete is a mixture of coarse (stone or brick chips) and fine (generally sand or crushed stone) aggregates with a paste of binder material (usually Portland cement) and water. This book explores the latest advances in the field of this subject. The subject matter, both as regards to the arrangement of chapters as well as contents is designed to meet the requirements of students at the undergraduate and postgraduate levels."